2015
DOI: 10.3835/plantgenome2014.08.0041
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptome Profile for Developing Seed of Polyploid Cotton

Abstract: Cotton ranks among the world's important oilseed crops, yet relative to other oilseeds there are few studies of oil-related biosynthetic and regulatory pathways. We present global transcriptome analyses of cotton seed development using RNA-seq and four developmental time-points. Because Upland cotton (Gossypium hirsutum L.) is an allopolyploid containing two genomes (A/D), we partitioned expression into the individual contributions of each homeologous gene copy. Data were explored with respect to genic and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 66 publications
(72 reference statements)
7
38
0
Order By: Relevance
“…The results from RNA-seq analysis also show that while both homeologs of the GoPGF (synonym CGF3) gene are expressed in the developing embryos of glanded cotton, the A subgenome homeolog is more active, thus providing confirmation for the earlier contention that Gl 2 is expressed at higher level compared to Gl 3 gene in glanded cotton (Lee, 1965). Hovav et al (2015) conducted global transcriptome analysis on developing seeds of G. hirsutum (TM1) at 10, 20, 30 and 40 dpa and found that about 20% of the genes showed homeolog expression bias. This group also observed that the ACGF3 homeolog in TM1 had higher level of expression than DCGF3 in the seeds at 30-and 40-dpa.…”
Section: -3supporting
confidence: 58%
See 1 more Smart Citation
“…The results from RNA-seq analysis also show that while both homeologs of the GoPGF (synonym CGF3) gene are expressed in the developing embryos of glanded cotton, the A subgenome homeolog is more active, thus providing confirmation for the earlier contention that Gl 2 is expressed at higher level compared to Gl 3 gene in glanded cotton (Lee, 1965). Hovav et al (2015) conducted global transcriptome analysis on developing seeds of G. hirsutum (TM1) at 10, 20, 30 and 40 dpa and found that about 20% of the genes showed homeolog expression bias. This group also observed that the ACGF3 homeolog in TM1 had higher level of expression than DCGF3 in the seeds at 30-and 40-dpa.…”
Section: -3supporting
confidence: 58%
“…Hovav et al . () conducted global transcriptome analysis on developing seeds of G. hirsutum (TM1) at 10, 20, 30 and 40 dpa and found that about 20% of the genes showed homeolog expression bias. This group also observed that the ACGF3 homeolog in TM1 had higher level of expression than DCGF3 in the seeds at 30‐ and 40‐dpa.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, acetyl-CoA carboxylase (ACCase) (E.C. 6.4.1.2) is an important enzyme, which catalyze acetyl-CoA to produce malonyl-CoA, and can be served as a committed step for de novo fatty acid biosynthesis in plastid (Sasaki and Nagano, 2004; Fukuda et al, 2013; Ran et al, 2015; Sood and Chauhan, 2015). In dicotyledon and non-graminaceous monocotyledon plants, plastidial ACCase is a multi-subunit complex comprised of four different polypeptides (biotin carboxyl carrier protein, BCCP; biotin carboxylase, BC; α- and β-carboxyltransferase subunits, α-CT and β-CT) with the exception of rapeseed plastid, which contains multifunctional ACCase comprised of a large multifunctional polypeptide (Elborough et al, 1996; Schulte et al, 1997; Sasaki and Nagano, 2004; Cui et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with these methods, high-throughput RNA sequencing (RNA-seq) can provide information on whole-genome gene expression with low background signals, more accurate quantification, a large dynamic range in expression levels and high levels of reproducibility [ 21 ]. In recent years, RNA-seq has been frequently used to investigate the transcriptomes of plant seeds, such as cotton [ 22 ], wheat [ 23 ], Brassica napus [ 24 ] and chrysanthemum [ 25 ].…”
Section: Introductionmentioning
confidence: 99%